Negative pole piece, battery monomer, battery and electric device

By adding silicon-based material and small-particle binder to the negative electrode film layer of the lithium-ion battery, and adding graphite to the negative electrode active material, the problem of volume expansion of the lithium-ion battery during circulation is solved, and the battery energy is improved Density and rate performance meet the long-term battery life of electric vehicles.

CN119230830APending Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310797700.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Lithium-ion batteries have serious volume expansion problems during circulation, resulting in poor circulation and rate performance, which cannot meet the long battery life of electric vehicles.

Method used

Add silicon-based material and binder with an average volume particle size of 0.1-0.8 μm to the negative electrode film layer. By increasing the active bonding site and filling the large pore area, the adhesive force is improved to inhibit volume expansion and the activity in the negative electrode is also improved. Graphite is added to the material to improve conductivity.

Benefits of technology

It significantly improves the energy density, power and circulation performance of the battery, takes into account high energy density and fast charging performance, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230830A_ABST
    Figure CN119230830A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a negative pole piece, a battery monomer, a battery and an electric device. The negative electrode plate comprises a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector; the negative electrode film layer comprises a negative electrode active material and a binder, and the negative electrode active material comprises a silicon-based material; wherein the average volume particle size Dv50 of the binder is 0.1 to 0.8 [mu] m. According to the technical scheme provided by the invention, the battery can give consideration to relatively high energy density and power and relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and more specifically, to a negative electrode plate, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have been used in more and more fields, such as wind power, hydropower, thermal power generation, solar power stations and other energy storage power supply fields, as well as electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. While lithium-ion batteries have made great progress, higher requirements have been put forward for their performance in all aspects.

[0003] Therefore, how to improve the performance of lithium-ion batteries is an urgent problem to be solved. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a negative electrode plate, a battery cell, a battery and an electrical device, wherein the battery has high energy density, power and good cycle performance.

[0005] In a first aspect, a negative electrode plate is provided, comprising a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector; the negative electrode film layer comprises a negative electrode active material and a binder, and the negative electrode active material comprises a silicon-based material; wherein the volume average particle size Dv50 of the binder is 0.1-0.8 μm.

[0006] In the embodiment of the present application, the negative electrode plate includes a negative electrode film layer, further, the negative electrode film layer includes a negative electrode active material and a binder, and further, the negative electrode active material includes a silicon-based material, wherein the volume average particle size Dv50 of the binder is 0.1-0.8 μm. By adding silicon-based materials and binders to the negative electrode film layer, on the one hand, the theoretical specific capacity of silicon-based materials is higher, which is beneficial to improving the energy density of the battery; on the other hand, silicon-based materials are harder and not easily crushed when cold pressed, and the particle shape is relatively irregular, with certain gaps between particles. Therefore, negative electrode sheets containing silicon-based materials generally have a larger porosity. Adding a binder with a volume average particle size Dv50 of 0.1-0.8μm to the negative electrode film layer can not only increase the active bonding sites, but also effectively fill and bond the large pore areas of the electrode sheet, improve the bonding force to inhibit the serious volume expansion of the silicon-based material during the battery cycle, and maintain the stability of the active material during the cycle process, and minimize the amount of binder used, thereby improving the cycle performance and power of the battery, so that the battery has both higher energy density, power and better cycle performance.

[0007] In a possible implementation, the volume average particle size Dv50 of the binder is 0.1-0.5 μm. Optionally, the volume average particle size Dv50 of the binder is 0.1-0.3 μm.

[0008] In the embodiment of the present application, in order to suppress the volume expansion of the silicon-based material during the battery cycle, a binder with a volume average particle size Dv50 of 0.1-0.8 μm is added to the negative electrode film layer. Furthermore, by making the volume average particle size Dv50 of the binder 0.1-0.5 μm, especially 0.1-0.3 μm, the bonding force between the negative electrode active materials can be further improved, thereby further improving the cycle stability of the negative electrode active materials during the cycle process, thereby obtaining a battery with high bonding force, high power, high energy density, and long cycle performance.

[0009] In a possible implementation, based on 100 parts by weight of the negative electrode film layer, the weight of the binder is 1-5 parts by weight. Optionally, the weight of the binder is 2-4 parts by weight.

[0010] In the embodiment of the present application, in order to suppress the volume expansion of the silicon-based material during the battery cycle, a binder with a smaller particle size is added to the negative electrode film layer so that the binder fills the large pore area in the negative electrode film layer. By making the mass proportion of the binder in the negative electrode film layer 1%-5%, especially 2%-4%, the bonding force between the negative electrode active materials can be improved to suppress the volume expansion of the negative electrode sheet, and the reduction in battery energy density caused by excessive binder content can be reduced.

[0011] In a possible implementation manner, the porosity of the negative electrode plate is 15%-60%. Optionally, the porosity of the negative electrode plate is 20%-45%.

[0012] In the embodiments of the present application, the theoretical capacity of silicon-based materials is relatively high, so when the battery uses silicon-based materials as negative electrode active materials, the battery has a higher energy density. However, for silicon-based materials, if the porosity of the negative electrode plate is too large, the negative electrode plate will undergo a more serious volume expansion effect during the battery cycle, which will cause the bonding and electrical contact between the negative electrode active materials to deteriorate. By making the porosity of the negative electrode plate 15%-60%, especially 20%-45%, it is beneficial for the battery to have better energy density and fast charging performance, and can also reduce the poor bonding and electrical contact between the negative electrode active materials caused by excessive porosity.

[0013] In some embodiments, the binder contains a hydrophilic group; optionally, the hydrophilic group includes at least one of sulfonic acid group, phosphoric acid group, hydroxyl group, carboxyl group, amide group, amino group, aldehyde group, carbonyl group, cyano group, and acid anhydride.

[0014] In the embodiment of the present application, in order to improve the adhesion of the negative electrode plate to suppress the serious volume expansion of the silicon-based material during the battery cycle, a binder with a volume average particle size Dv50 of 0.1-0.8 μm is added to the negative electrode plate. However, if the particle size of the binder is small, it is easy to cause the binder to float during the slurry coating and drying process, and thus cannot play a bonding role. Therefore, by making the binder contain at least one of sulfonic acid group, phosphoric acid group, hydroxyl group, carboxyl group, amide group, amino group, aldehyde group, carbonyl group, cyano group, and acid anhydride, these hydrophilic groups can increase the interaction between the binder and the silicon-based material and graphite material, thereby effectively modifying the small particle size binder to float during the coating and drying process of the plate, prompting the binder to stay evenly in the gap of the silicon-based material, thereby effectively improving the cohesion of the negative electrode plate.

[0015] In some embodiments, the silicon-based material includes at least one of the following functional groups: carboxyl, hydroxyl, aldehyde, carbonyl.

[0016] In the embodiments of the present application, by making the silicon-based material include at least one functional group of carboxyl, hydroxyl, aldehyde, and carbonyl, these functional groups can interact with the monomers or functional groups in the binder, thereby enhancing the bonding effect between the silicon-based material and the binder.

[0017] In some embodiments, the specific surface area SSA of the silicon-based material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 2m 2 / g≤SSA≤4m 2 / g.

[0018] In the embodiment of the present application, by making the specific surface area of ​​the silicon-based material meet the above range, the bonding effect between the silicon-based material and the binder can be further strengthened, and the material has good kinetic properties, which is beneficial to the first-cycle coulomb efficiency of the battery.

[0019] In a possible implementation, the volume average particle size Dv50 of the silicon-based material is 5-20 μm. Optionally, the volume average particle size Dv50 of the silicon-based material is 8-15 μm.

[0020] In the embodiment of the present application, by making the volume average particle size Dv50 of the silicon-based material 5-20 μm, especially 8-15 μm, the negative electrode plate can have a larger porosity to improve the fast charging performance of the battery, and the adhesion between the negative electrode active materials caused by the excessively large particle size of the silicon-based material can be reduced.

[0021] In some embodiments, the silicon-based material includes: carbon-based particles including a three-dimensional network cross-linked pore structure; and silicon-based nanoparticles, at least a portion of which is disposed in the three-dimensional network cross-linked pore structure.

[0022] In the embodiments of the present application, the carbon matrix particles have a stable porous skeleton structure with strong supporting capacity, which is manifested as high stress capacity, and has excellent mechanical properties and conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for setting silicon-based nanoparticles and can be used for large-scale silicon storage; when the porous carbon matrix particles are composited with silicon-based nanoparticles, the silicon-based nanoparticles are not easy to agglomerate and can be evenly dispersed in the pores of the carbon matrix particles; after the carbon matrix particles are composited with silicon-based nanoparticles, the conductivity of the silicon-carbon composite material can be improved, and at the same time, the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material, and improving the cycle stability and lithium storage capacity of the silicon-carbon composite material, thereby improving the cycle performance and energy density of the battery when the silicon-carbon composite material is applied to batteries.

[0023] In one possible embodiment, when the gas adsorption and desorption method is used for testing, the total pore volume of the pores with a pore size greater than 100 nm in the carbon matrix particles is recorded as V1 cm 3 / g, then V1≥0.01, optionally, 0.01≤V1≤0.5; and / or, when the gas adsorption and desorption method is used for testing, the total pore volume of the pores with a pore diameter of less than or equal to 100 nm in the carbon matrix particles is recorded as V2 cm 3 / g, then V2≥0.05, optionally, 0.05≤V2≤1.1.

[0024] In the embodiments of the present application, when the porosity of the carbon matrix particles meets the above range, the pores occupy an appropriate volume of the skeleton, which can not only ensure the stability of the skeleton structure but also meet the capacity of deposited silicon. Silicon-based nanoparticles are attached to the pores, and the silicon-based nanoparticles and porous carbon matrix particles can work synergistically to improve the capacity and conductivity of the silicon-carbon composite material.

[0025] In a possible implementation, the silicon-based material includes at least one of a silicon-carbon material and a composite of a silicon-carbon material and a silicon-oxygen material.

[0026] In the embodiments of the present application, by adding silicon-based materials, especially silicon-carbon materials or a composite of silicon-oxygen materials and silicon-oxygen materials, to the negative electrode active material, the energy density of the battery can be improved.

[0027] In a possible implementation manner, the silicon-oxygen material includes SiO x , where 0.4≤x≤1.6.

[0028] In the embodiment of the present application, the silicon-oxygen material in the silicon-based material not only has high theoretical capacity and excellent stability, but also has the advantages of low cost, non-toxicity and environmental friendliness. x , where 0.4≤x≤1.6, can further improve the performance of the battery.

[0029] In a possible implementation, the silicon-carbon material includes a silicon-carbon composite; based on the total mass of the silicon-carbon composite, a ratio of a mass content B of carbon element to a mass content A of silicon element in the silicon-carbon composite is 1.3≤B / A≤2.

[0030] In the embodiment of the present application, the silicon-carbon material has a higher theoretical capacity and better cycle performance. By making the silicon-carbon material include a silicon-carbon composite, wherein the ratio of the mass proportion of silicon element in the silicon-carbon composite A to the mass proportion of carbon element in the silicon-carbon composite B is 1.3≤B / A≤2, the performance of the battery can be further improved.

[0031] In a possible embodiment, the binder includes at least one of polystyrene butadiene copolymers and modifications thereof, polystyrene-acrylates and modifications thereof, polyacrylate copolymers and modifications thereof, polyurethane copolymers and modifications thereof, butadiene and acrylonitrile copolymers and modifications thereof, polytetrafluoroethylene and modifications thereof, and polyvinylidene fluoride and modifications thereof.

[0032] In the embodiments of the present application, by using at least one of polystyrene butadiene copolymers and their modifications, polystyrene-acrylates and their modifications, polyacrylate copolymers and their modifications, polyurethane copolymers and their modifications, butadiene and acrylonitrile copolymers and their modifications, polytetrafluoroethylene and their modifications, polyvinylidene fluoride and their modifications with good bonding strength as a binder, it helps to further improve the bonding strength between the negative electrode active material and the negative electrode current collector.

[0033] In a possible implementation, based on 100 parts by weight of the negative electrode film layer, the weight of the silicon-based material is 25-50 parts by weight. Optionally, the weight of the silicon-based material is 30-40 parts by weight.

[0034] In the embodiment of the present application, in order to improve the energy density and rate performance of the battery, silicon-based materials are added to the negative electrode active materials. However, the greater the content of silicon-based materials, the greater the porosity of the negative electrode sheet, and the worse the bonding force between the negative electrode active materials. Therefore, by making the mass proportion of silicon-based materials in the negative electrode film layer 25%-50%, especially 30%-40%, it is beneficial to further improve the performance of the battery.

[0035] In a possible implementation, the negative electrode active material further comprises graphite; wherein, based on 100 parts by weight of the negative electrode film layer, the weight of the graphite is 45-70 parts by weight, and optionally, the weight of the graphite is 55-65 parts by weight.

[0036] In the embodiment of the present application, the silicon-based material has a high theoretical capacity, but its conductivity is poor. Therefore, if only the silicon-based material is used as the negative electrode active material of the battery, the conductivity of the battery will be very poor. By adding graphite with good conductivity to the negative electrode active material and making the mass proportion of graphite in the negative electrode film layer 45%-70%, especially 55%-65%, the battery can maintain good cycle performance.

[0037] In a possible implementation, the compaction density of the negative electrode plate is 1.0-2.2 g / cm 3 Optionally, the compaction density of the negative electrode plate is 1.2-1.8 g / cm 3 .

[0038] In the embodiment of the present application, by making the compaction density of the negative electrode sheet 1.0-2.2g / cm 3 , especially 1.2-1.8g / cm 3 , which can further improve the energy density of the battery.

[0039] In a possible implementation manner, the thickness of the negative electrode plate is 60-150 μm. Optionally, the thickness of the negative electrode plate is 90-130 μm.

[0040] In the embodiment of the present application, the energy density of the battery can be further improved by making the thickness of the negative electrode plate 60-150 μm, especially 90-130 μm.

[0041] The second aspect of the present application provides a battery cell, comprising the negative electrode plate described in any embodiment of the first aspect of the present application.

[0042] In a possible implementation, the battery cell further includes a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode film layer provided on at least one side of the positive electrode collector, and the positive electrode film layer includes a positive electrode active material.

[0043] In one possible embodiment, the positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y, wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.02.

[0044] A third aspect of the present application provides a battery, comprising the battery cell described in the second aspect of the present application.

[0045] The fourth aspect of the present application provides an electrical device, comprising the battery according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0047] Figure 1 This is a schematic structural diagram of a negative electrode sheet according to an embodiment of the present application;

[0048] Figure 2 A schematic diagram of a battery cell according to an embodiment of the present application;

[0049] Figure 3 A schematic diagram of the structure of a battery cell according to an embodiment of the present application;

[0050] Figure 4 A schematic diagram of a battery according to an embodiment of the present application;

[0051] Figure 5 This is a schematic diagram of the structure of a battery according to one embodiment of the present application;

[0052] Figure 6 It is a schematic structural diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0053] The following describes the embodiments of the negative electrode sheet, battery cell, battery and electric device of the present application in detail with appropriate reference to the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually the same structure may be omitted. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0054] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a specific range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0055] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0056] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0057] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, and can be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0058] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.

[0059] The terms "above", "below", "greater than" or "less than" as used in this application include the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".

[0060] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] Lithium-ion batteries are widely used in consumer electronics due to their high energy density, power and long cycle performance. In recent years, with the continuous development of electric vehicles and energy storage systems, people's requirements for battery cycle performance and energy density are also increasing.

[0062] At present, the capacity of lithium-ion batteries using graphite materials as negative electrode active materials has gradually failed to meet the requirements of long-range electric vehicles. Silicon-based materials have become the most promising negative electrode materials for the next generation of lithium-ion batteries due to their large specific capacity, low discharge platform, and rich energy storage. However, silicon-based materials are severely limited in their commercial application due to their own factors. First of all, silicon-based materials have severe volume expansion during battery cycling. The large volume change during lithium insertion and extraction can easily lead to particle pulverization, separation of active materials from the negative electrode current collector, and continuous growth of SEI film, ultimately leading to poor cycle performance and poor rate performance. Therefore, how to make batteries using silicon-based materials have better cycle performance and rate performance is an urgent problem to be solved.

[0063] In view of this, the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector. By adding a silicon-based material and a binder to the negative electrode active material of the negative electrode film layer, and making the volume average particle size Dv50 of the binder 0.1-0.8μm, it is possible to increase the active bonding sites, and effectively fill and bond the large pore areas of the plate, improve the bonding force to inhibit the serious volume expansion of the silicon-based material during the battery cycle, and maintain the stability of the active material during the cycle process, and minimize the amount of binder, so that the battery has a higher energy density while also having better rate and cycle performance.

[0064] The negative electrode sheet, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.

[0065] In addition, the technical solution of the present application is applicable to various types of batteries such as lithium-ion batteries, lithium metal batteries, sodium-ion batteries, etc., and the present application does not limit this; for the convenience of description, the following description will take lithium-ion batteries as an example.

[0066] [Negative electrode]

[0067] The first aspect of the present application provides a negative electrode plate, Figure 1 Schematic diagram of the structure of the negative electrode sheet of one embodiment of the present application. Figure 1 As shown, the negative electrode plate 121 includes a negative electrode current collector 122 and a negative electrode film layer 123 provided on at least one side of the negative electrode current collector 122; the negative electrode film layer 123 includes a negative electrode active material and a binder, and the negative electrode active material includes a silicon-based material; wherein the volume average particle size Dv50 of the binder is 0.1-0.8 μm.

[0068] Adding silicon-based materials and binders to the negative electrode film layer 123 and making the volume average particle size Dv50 of the binder 0.1-0.8 μm can improve the adhesion of the negative electrode sheet and reduce the expansion of the negative electrode sheet, thereby improving the performance of the battery.

[0069] In the embodiments of the present application, silicon-based materials refer to materials grown through different process steps using silicon materials as substrates or bases, including silicon materials on insulating layers, germanium silicon materials, porous silicon, microcrystalline silicon, and other compound semiconductor materials grown heteroepitaxially using silicon as a substrate.

[0070] Generally, a battery cell includes a positive electrode, a separator, a negative electrode, and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive and negative electrodes. The electrolyte plays the role of transferring ions between the positive and negative electrodes. The separator is set between the positive and negative electrodes, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0071] It should be noted here that the “positive electrode sheet” and “negative electrode sheet” mentioned in the embodiments of the present application refer to the positive electrode sheet and the negative electrode sheet as a whole including active materials, current collectors or other additives.

[0072] The negative electrode sheet 121 includes a negative electrode current collector 122 and a negative electrode film layer 123 disposed on at least one surface of the negative electrode current collector 122 , wherein the negative electrode film layer 123 includes a negative electrode active material.

[0073] As an example, the negative electrode current collector 122 has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer 123 is disposed on any one or both of the two opposite surfaces of the negative electrode current collector 122 .

[0074] In the above solution, the negative electrode sheet 121 includes a negative electrode film layer 123, and further, the negative electrode film layer 123 includes a negative electrode active material and a binder, and further, the negative electrode active material includes a silicon-based material, wherein the volume average particle size Dv50 of the binder is 0.1-0.8 μm. By adding silicon-based materials and binders to the negative electrode film layer, on the one hand, silicon-based materials have a higher theoretical specific capacity, which is beneficial to improving the energy density of the battery; on the other hand, silicon-based materials are harder and not easily crushed when cold pressed, and the particle shape is relatively irregular, with certain gaps between particles. Therefore, negative electrode sheets containing silicon-based materials generally have a larger porosity. Adding a binder with a volume average particle size Dv50 of 0.1-0.8μm to the negative electrode film layer can not only increase the active bonding sites, but also effectively fill and bond the large pore areas of the electrode sheet, improve the bonding force to inhibit the serious volume expansion of the silicon-based material during the battery cycle, and maintain the stability of the active material during the cycle process, and minimize the amount of binder, thereby improving the cycle performance and power of the battery, so that the battery has both higher energy density, power and better cycle performance.

[0075] In some embodiments, the volume average particle size Dv50 of the binder is 0.1-0.5 μm. Optionally, the volume average particle size Dv50 of the binder is 0.1-0.3 μm.

[0076] In the above scheme, in order to suppress the volume expansion of the silicon-based material during the battery cycle, a binder with a volume average particle size Dv50 of 0.1-0.8 μm is added to the negative electrode film layer. Furthermore, by making the volume average particle size Dv50 of the binder 0.1-0.5 μm, especially 0.1-0.3 μm, the bonding force between the negative electrode active materials can be further improved, thereby further improving the cycle stability of the negative electrode active materials during the cycle process, thereby obtaining a battery with high bonding force, high power, high energy density and long cycle performance.

[0077] It should be noted here that the volume average particle size Dv50 of the binder may be 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, or any value within the range consisting of the above values.

[0078] In some embodiments, based on 100 parts by weight of the negative electrode film layer 123 , the weight portion of the binder is 1-5 parts by weight. Optionally, the weight portion of the binder is 2-4 parts by weight.

[0079] In the above scheme, in the embodiment of the present application, in order to suppress the volume expansion of the silicon-based material during the battery cycle, a binder with a smaller particle size is added to the negative electrode film layer so that the binder fills the large pore area in the negative electrode film layer. By making the mass proportion of the binder in the negative electrode film layer 1%-5%, especially 2%-4%, it can not only improve the bonding force between the negative electrode active materials to suppress the volume expansion of the negative electrode sheet, but also reduce the reduction in battery energy density caused by excessive binder content.

[0080] It should be noted here that, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the binder can be 1 part by weight, 1.5 parts by weight, 2 parts by weight, 4 parts by weight, and any value within the range of the above values.

[0081] In some embodiments, the porosity of the negative electrode sheet 121 is 15%-60%. Optionally, the porosity of the negative electrode sheet 121 is 20%-45%.

[0082] In the above scheme, in the embodiment of the present application, the theoretical capacity of the silicon-based material is relatively high, so when the battery uses silicon-based materials as the negative electrode active material, the battery has a higher energy density. However, for silicon-based materials, if the porosity of the negative electrode plate is too large, the negative electrode plate will undergo a more serious volume expansion effect during the battery cycle, which will cause the bonding and electrical contact between the negative electrode active materials to deteriorate. By making the porosity of the negative electrode plate 15%-60%, especially 20%-45%, it is beneficial for the battery to have better energy density and fast charging performance, and can also reduce the poor bonding and electrical contact between the negative electrode active materials caused by excessive porosity.

[0083] It should be noted here that the porosity of the negative electrode sheet 121 can be 18%, 25%, 30%, 40% or any value within the range of the above values.

[0084] In some embodiments, the binder contains a hydrophilic group; optionally, the hydrophilic group includes at least one of sulfonic acid group, phosphoric acid group, hydroxyl group, carboxyl group, amide group, amino group, aldehyde group, carbonyl group, cyano group, and acid anhydride.

[0085] Hydrophilic groups, also known as oleophobic groups, have atomic groups that are soluble in water or easily have an affinity with water. They may attract water molecules or dissolve in water, and the solid surface with such functional groups is easily wetted by water.

[0086] In the embodiment of the present application, in order to improve the adhesion of the negative electrode plate 121 to suppress the serious volume expansion of the silicon-based material during the battery cycle, a binder with a volume average particle size Dv50 of 0.1-0.8 μm is added to the negative electrode plate 121. However, if the particle size of the binder is small, it is easy to cause the binder to float during the slurry coating and drying process, and thus cannot play a bonding role. Therefore, by making the binder contain at least one of sulfonic acid group, phosphoric acid group, hydroxyl group, carboxyl group, amide group, amino group, aldehyde group, carbonyl group, cyano group, and acid anhydride, these hydrophilic groups can increase the interaction between the binder and the silicon-based material and graphite material, thereby effectively modifying the small particle size binder to float during the coating and drying process of the plate, prompting the binder to stay evenly in the gap of the silicon-based material, thereby effectively improving the cohesion of the negative electrode plate.

[0087] In some embodiments, the silicon-based material includes at least one of the following functional groups: carboxyl, hydroxyl, aldehyde, carbonyl.

[0088] In the embodiments of the present application, by making the silicon-based material include at least one functional group of carboxyl, hydroxyl, aldehyde, and carbonyl, these functional groups can interact with the monomers or functional groups in the binder, thereby enhancing the bonding effect between the silicon-based material and the binder.

[0089] In some embodiments, the specific surface area SSA of the silicon-based material satisfies: 2 m 2 / g≤SSA≤10m 2 / g; optionally, 2m 2 / g≤SSA≤4m 2 / g.

[0090] In the embodiment of the present application, by making the specific surface area of ​​the silicon-based material meet the above range, the bonding effect between the silicon-based material and the binder can be further strengthened, and the material has good kinetic properties, which is beneficial to the first-cycle coulomb efficiency of the battery.

[0091] It should be noted here that the specific surface area of ​​silicon-based materials can be 2m 2 / g, 3m 2 / g, 5m 2 / g, 8m 2 / g and any value within the range consisting of the above values.

[0092] In some embodiments, the volume average particle size Dv50 of the silicon-based material is 5-20 μm. Optionally, the volume average particle size Dv50 of the silicon-based material is 8-15 μm.

[0093] In the above scheme, by making the volume average particle size Dv50 of the silicon-based material 5-20μm, especially 8-15μm, the negative electrode plate can have a larger porosity to improve the fast charging performance of the battery, and the adhesion between the negative electrode active materials caused by the excessively large particle size of the silicon-based material can be reduced.

[0094] It should be noted here that the volume average particle size Dv50 of the silicon-based material can be 5 μm, 8 μm, 10 μm, 18 μm, and any value within the range consisting of the above values.

[0095] In some embodiments, the silicon-based material includes: carbon matrix particles including a three-dimensional network cross-linked pore structure; and silicon-based nanoparticles, at least a portion of which is disposed in the three-dimensional network cross-linked pore structure.

[0096] The three-dimensional network cross-linked pore structure generally refers to a structure in which two or more pores are interconnected or interlaced and share pore volume in the pore structure formed by carbon matrix particles.

[0097] In the embodiments of the present application, the carbon matrix particles have a stable porous skeleton structure with strong supporting capacity, which is manifested as high stress capacity, and has excellent mechanical properties and conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for setting silicon-based nanoparticles and can be used for large-scale silicon storage; when the porous carbon matrix particles are composited with silicon-based nanoparticles, the silicon-based nanoparticles are not easy to agglomerate and can be evenly dispersed in the pores of the carbon matrix particles; after the carbon matrix particles are composited with silicon-based nanoparticles, the conductivity of the silicon-carbon composite material can be improved, and at the same time, the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material, and improving the cycle stability and lithium storage capacity of the silicon-carbon composite material, thereby improving the cycle performance and energy density of the battery when the silicon-carbon composite material is applied to batteries.

[0098] In one possible embodiment, when the gas adsorption-desorption method is used for testing, the total pore volume of the pores with a pore size greater than 100 nm in the carbon matrix particles is recorded as V1 cm 3 / g, then V1≥0.01, optionally, 0.01≤V1≤0.5; and / or, when the gas adsorption and desorption method is used for testing, the total pore volume of the pores with a pore size of less than or equal to 100 nm in the carbon matrix particles is recorded as V2cm 3 / g, then V2≥0.05, optionally, 0.05≤V2≤1.1.

[0099] In the embodiments of the present application, when the porosity of the carbon matrix particles meets the above range, the pores occupy an appropriate volume of the skeleton, which can not only ensure the stability of the skeleton structure but also meet the capacity of deposited silicon. Silicon-based nanoparticles are attached to the pores, and the silicon-based nanoparticles and porous carbon matrix particles can work synergistically to improve the capacity and conductivity of the silicon-carbon composite material.

[0100] It should be noted here that V1 can be 0.01, 0.05, 0.1, 0.5, and any value in the range of the above values; V1 can be 0.05, 0.2, 0.5, 1, and any value in the range of the above values.

[0101] In some embodiments, the silicon-based material includes at least one of a silicon-carbon material, a composite of a silicon-carbon material and a silicon-oxygen material.

[0102] In the above scheme, by adding silicon-based materials, especially silicon-carbon materials or a composite of silicon-oxygen materials and silicon-oxygen materials, to the negative electrode active material, it is beneficial to improve the energy density of the battery.

[0103] It should be noted here that silicon-oxygen material refers to a compound composed of silicon and oxygen; silicon-carbon material refers to a compound composed of silicon and carbon.

[0104] In some embodiments, the silicon-oxygen material comprises SiO x , where 0.4≤x≤1.6.

[0105] In the above scheme, the silicon-oxygen material in the silicon-based material not only has high theoretical capacity and excellent stability, but also has the advantages of low cost, non-toxicity and environmental friendliness. x , which can further improve the performance of the battery.

[0106] It should be noted here that silicon oxide materials include but are not limited to the following substances: SiO 0.4 、SiO 0.6 、SiO、SiO 1.5 .

[0107] In some embodiments, the silicon-carbon material includes a silicon-carbon composite; based on the total mass of the silicon-carbon composite, a ratio of a mass content A of silicon element to a mass content B of carbon element in the silicon-carbon composite is 1.3≤B / A≤2.

[0108] In the above scheme, the silicon-carbon material has a higher theoretical capacity and better cycle performance. By making the silicon-carbon material include a silicon-carbon composite, wherein the ratio of the mass proportion A of the silicon element in the silicon-carbon composite to the mass proportion B of the carbon element in the silicon-carbon composite is 1.3≤B / A≤2, the performance of the battery can be further improved.

[0109] It should be noted here that, in the silicon-carbon material, the mass ratio B / A of carbon element to silicon element can be 1.3, 1.5, 1.7, 3 and any value within the range of the above values.

[0110] In some embodiments, the binder includes at least one of polystyrene butadiene copolymer and its modifications, polystyrene-acrylate and its modifications, polyacrylate copolymer and its modifications, polyurethane copolymer and its modifications, butadiene and acrylonitrile copolymer and its modifications, polytetrafluoroethylene and its modifications, polyvinylidene fluoride and its modifications.

[0111] In the above scheme, by using at least one of polystyrene butadiene copolymer and its modified products, polystyrene-acrylate and its modified products, polyacrylate copolymer and its modified products, polyurethane copolymer and its modified products, butadiene and acrylonitrile copolymer and its modified products, polytetrafluoroethylene and its modified products, polyvinylidene fluoride and its modified products with good bonding strength as a binder, it helps to further improve the bonding strength between the negative electrode active material and the negative electrode collector 122.

[0112] In some embodiments, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the silicon-based material is 25-50 parts by weight. Optionally, the weight of the silicon-based material is 30-40 parts by weight.

[0113] In the above scheme, in the embodiment of the present application, in order to improve the energy density of the battery, silicon-based materials are added to the negative electrode active materials, but the greater the content of silicon-based materials, the greater the porosity of the negative electrode sheet, and the worse the adhesion between the negative electrode active materials. Therefore, by making the mass proportion of silicon-based materials in the negative electrode film layer 25%-50%, especially 30%-40%, it is beneficial to further improve the performance of the battery.

[0114] It should be noted that, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the silicon-based material can be 25 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, and any value within the range of the above values.

[0115] In some embodiments, the negative electrode active material further comprises graphite; wherein, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the graphite is 45-70 parts by weight, and optionally, the weight of the graphite is 55-65 parts by weight.

[0116] In the above scheme, silicon-based materials have a high theoretical capacity, but their conductivity is poor. Therefore, if only silicon-based materials are used as the negative electrode active material of the battery, the conductivity of the battery will be very poor. By adding graphite with good conductivity to the negative electrode active material and making the mass proportion of graphite in the negative electrode film layer 123 45%-70%, especially 55%-65%, the battery can maintain good cycle performance.

[0117] It should be noted here that, based on 100 parts by weight of the negative electrode film layer 123 , the weight of graphite can be 50 parts by weight, 58 parts by weight, 65 parts by weight, 72 parts by weight, and any value within the range of the above values.

[0118] In some embodiments, the compaction density of the negative electrode sheet 121 is 1.0-2.2 g / cm 3 Optionally, the compaction density of the negative electrode sheet 121 is 1.2-1.8 g / cm 3 .

[0119] In the above scheme, by making the compaction density of the negative electrode sheet 121 1.0-2.2 g / cm 3 , especially 1.2-1.8g / cm 3 , which can further improve the energy density of the battery.

[0120] It should be noted that the compaction density of the negative electrode sheet 121 can be 1g / cm 3 , 1.5g / cm 3 , 2.2g / cm 3 and any value within the range consisting of the above values.

[0121] In some embodiments, the thickness d1 of the negative electrode sheet 121 is 60-150 μm. Optionally, the thickness d1 of the negative electrode sheet 121 is 90-130 μm.

[0122] In the above solution, by making the thickness d1 of the negative electrode sheet 121 to be 60-150 μm, especially 90-130 μm, the energy density of the battery can be further improved.

[0123] It should be noted here that the thickness d1 of the negative electrode sheet 121 can be 60 μm, 80 μm, 100 μm, 120 μm, or any value within the range of the above values.

[0124] In some embodiments, the negative electrode current collector 122 may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0125] In some embodiments, the negative electrode active material may also include negative electrode active materials for batteries known in the art. As an example, in addition to silicon-based materials, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, lithium titanate, etc. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. In addition, the silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0126] In some embodiments, the binder may be selected from at least one of styrene-butadiene rubber (SBR), styrene-butadiene block copolymer (SBS), acrylonitrile-butadiene-styrene copolymer (ABS), polyurethane (PU), and polytetrafluoroethylene (PTFE).

[0127] In some embodiments, the negative electrode film layer 122 may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0128] In some embodiments, the negative electrode film layer 122 may further include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0129] In some embodiments, the negative electrode sheet 121 can be prepared in the following manner: the components for preparing the negative electrode sheet 121, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector 122, and after drying, cold pressing and other processes, the negative electrode sheet 121 can be obtained.

[0130] [Positive electrode]

[0131] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0132] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0133] In some embodiments, the positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.02.

[0134] It should be noted here that the positive electrode active materials include but are not limited to the following substances: Li 0.5 Ni 0.5 Co 0.1 Mn 0.4 O2、Li 0.5 (Ni 0.5 Co 0.1 Mn 0.4 ) 0.5 Zr 0.5 O 1.9 A 0.1 、LiNi 0.4 Co 0.3 Mn 0.3 O2.

[0135] It should be noted that in the positive electrode sheet, battery or electrical device, as the battery undergoes formation and circulation processes, lithium ions will be consumed, so the measured lithium content in the positive electrode active material may be less than 1. At the same time, if the positive electrode sheet and the negative electrode sheet are supplemented with lithium, the measured lithium content in the positive electrode active material may be greater than 1 after the battery undergoes formation and circulation processes.

[0136] Similarly, in the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0137] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0138] In some embodiments, the positive electrode active material may also adopt positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0139] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0140] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0141] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector. After drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0142] [Electrolytes]

[0143] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0144] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0145] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0146] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0147] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0148] [Isolation film]

[0149] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0150] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0151] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0152] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0153] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0154] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0155] Figure 3 Schematic diagram of the structure of a battery cell according to an embodiment of the present application. Figure 3As shown, the outer packaging of the battery cell 100 includes a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet 121 and the isolation film can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 100 can be one or more, and those skilled in the art can select according to specific actual needs.

[0156] In some embodiments, the battery cells 100 may also be assembled into a battery module. The battery module may contain one or more battery cells 100. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0157] Figure 4 is a schematic diagram of a battery according to one embodiment of the present application, Figure 5 Schematic diagram of the structure of a battery according to one embodiment of the present application. Figure 4 and Figure 5 The battery 400 may include a battery box and a plurality of battery cells 100 disposed in the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can cover the lower box body 402 and form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in the battery box in any manner.

[0158] In addition, the present application also provides an electric device, which includes at least one of the negative electrode plate 121, battery cell 100 or battery 400 provided in the present application. The negative electrode plate 121, battery cell 100 or battery 400 can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0159] For example, Figure 6 Schematic diagram of the structure of an electric device according to an embodiment of the present application. Figure 6As shown, the electrical device is a vehicle 1, and the vehicle 1 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 500, a controller 600 and a battery 400 may be arranged inside the vehicle 1, and the controller 600 is used to control the battery 400 to supply power to the motor 500. For example, a battery 400 may be arranged at the bottom, front or rear of the vehicle 1. The battery 400 may be used to power the vehicle 1, for example, the battery 400 may be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements during the start-up, navigation and operation of the vehicle 1. In another embodiment of the present application, the battery 400 may not only be used as an operating power source for the vehicle 1, but also as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0160] As the electrical device, the negative electrode sheet 121, the battery cell 100 or the battery 400 can be selected according to its usage requirements.

[0161] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell 100 or a battery 400 may be used.

[0162] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and the battery cell 100 may be used as a power source.

[0163] [Example]

[0164] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0165] [Example 1]

[0166] 1). Preparation of lithium-ion batteries

[0167] 1.1). Preparation of negative electrode sheet:

[0168] 1.11). Preparation of silicon-carbon material: comprising providing a gas containing a silicon precursor to carbon matrix particles having a carbon skeleton, and generating silicon nanoparticles attached to the carbon skeleton from the silicon precursor through chemical vapor deposition to obtain a carbon-silicon composite material (hereinafter referred to as silicon-carbon material).

[0169] 1.12) Preparation of binder: a part of emulsifier, a part of acrylate monomer, a part of styrene monomer and water are mixed to prepare pre-emulsion; another part of emulsifier, another part of acrylate monomer, another part of styrene monomer are mixed with water, and then an initiator is added to initiate polymerization to prepare seed emulsion; the pre-emulsion is added dropwise to the seed emulsion, and an initiator is added to carry out polymerization reaction to obtain a styrene-acrylic emulsion with a Dv50 particle size of 100nm-900nm of latex balls; wherein the total mass of the emulsifier is 0.7% to 5% of the total mass of the prepared monomers, and can be optionally 1% to 4.5%; the prepared monomers include acrylate monomers and styrene monomers. Based on the total mass of the prepared monomers, the styrene acrylic emulsion includes 30%-80% of styrene monomers, 20%-70% of acrylate monomers and 0-10% of functional monomers in terms of mass percentage; the functional monomers are added in the step of preparing the pre-emulsion and / or the seed emulsion. In this embodiment, the functional monomer is hydroxyethyl acrylate.

[0170] 1.13) Preparation of negative electrode sheet: The first active material artificial graphite and the second active material silicon carbon material, conductive agent acetylene black, conductive agent single-wall CNT, binder styrene acrylic emulsion, thickener CMC-Na are mixed in a proper amount of deionized water solvent system in a weight ratio of 64.9%:30%:1%:0.1%:3%:1% to obtain the negative electrode active material, and the negative electrode active material is coated on Cu foil, and then dried, cold pressed and cut to obtain the negative electrode sheet, wherein the weight of styrene acrylic emulsion is 3 parts by weight and the volume average particle size Dv50 is 0.15μm; the volume average particle size Dv50 of the second active material silicon carbon is 10μm and the specific surface area is 6m 2 / g.

[0171] 1.2) Preparation of positive electrode sheet: The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive agent carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are dissolved in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 96%:2%:2%, and the positive electrode active material is prepared after being fully stirred and mixed. The positive electrode active material is coated on Al foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0172] 1.3). Preparation of diaphragm: PE porous polymer film is used as the isolation membrane.

[0173] 1.4). Electrolyte: Dissolve EC / EMC / DMC in 1M LiPF6 at a volume ratio of 1:1:1 and stir evenly.

[0174] 1.5) Assembly: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and wind them to get the electrode assembly, and add electrolyte. Then hot press at 100℃ and 250MPa for 2min to get the lithium-ion battery.

[0175] [Example 2]

[0176] The preparation process of the lithium ion battery of Example 2 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder is 0.1 μm.

[0177] [Example 3]

[0178] The preparation process of the lithium ion battery of Example 3 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder is 0.3 μm.

[0179] [Example 4]

[0180] The preparation process of the lithium ion battery of Example 4 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder is 0.5 μm.

[0181] [Example 5]

[0182] The preparation process of the lithium ion battery of Example 5 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder is 0.8 μm.

[0183] [Example 6]

[0184] The preparation process of the lithium ion battery of Example 6 is substantially the same as that of Example 1, except that the weight part of the binder is 2 weight parts.

[0185] [Example 7]

[0186] The preparation process of the lithium ion battery of Example 7 is substantially the same as that of Example 1, except that the weight parts of the binder is 4 weight parts.

[0187] [Example 8]

[0188] The preparation process of the lithium ion battery of Example 8 is substantially the same as that of Example 1, except that the weight parts of the binder is 7 weight parts.

[0189] [Example 9]

[0190] The preparation process of the lithium ion battery of Example 9 is substantially the same as that of Example 1, except that the binder is styrene-butadiene rubber (SBR).

[0191] [Example 10]

[0192] The preparation process of the lithium ion battery of Example 10 is substantially the same as that of Example 1, except that the binder is polyurethane.

[0193] [Example 11]

[0194] The preparation process of the lithium-ion battery of Example 11 is basically the same as that of Example 1, except that the weight of the second active material is 20 parts by weight, and the weight ratio of the first active material artificial graphite, the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion, and the thickener CMC-Na is 74.9%:20%:1%:0.1%:3%:1%.

[0195] [Example 12]

[0196] The preparation process of the lithium-ion battery of Example 12 is basically the same as that of Example 1, except that the weight of the second active material is 40 parts by weight, and the weight ratio of the first active material artificial graphite, the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion, and the thickener CMC-Na is 44.9%:50%:1%:0.1%:3%:1%.

[0197] [Example 13]

[0198] The preparation process of the lithium ion battery of Example 13 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the second active material is 15 μm.

[0199] [Example 14]

[0200] The preparation process of the lithium ion battery of Example 14 is substantially the same as that of Example 1, except that the second active material is silicon dioxide.

[0201] [Example 15]

[0202] The preparation process of the lithium-ion battery of Example 15 is substantially the same as that of Example 1, except that the second active material is silicon oxide.

[0203] [Example 16]

[0204] The preparation process of the lithium-ion battery of Example 16 is basically the same as that of Example 1, except that there is no first active material, and the weight ratio of the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion (SAR), and the thickener CMC-Na is 94.9%:1%:0.1%:3%:1%.

[0205] [Example 17]

[0206] The preparation process of the lithium ion battery of Example 17 is basically the same as that of Example 1, except that no functional monomer is used in the preparation of the binder.

[0207] [Example 18]

[0208] The preparation process of the lithium ion battery of Example 18 is basically the same as that of Example 1, except that the functional monomer used in the preparation of the binder is acrylic acid.

[0209] [Example 19]

[0210] The preparation process of the lithium ion battery of Example 19 is basically the same as that of Example 1, except that the functional monomer used in the preparation of the binder is methacrylamide.

[0211] [Example 20]

[0212] The preparation process of the lithium ion battery of Example 20 is substantially the same as that of Example 1, except that the specific surface area of ​​the second active material is 4 m 2 / g.

[0213] [Comparative Example 1]

[0214] The preparation process of the lithium ion battery of Comparative Example 1 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder is 1 μm.

[0215] [Comparative Example 2]

[0216] The preparation process of the lithium ion battery of Comparative Example 2 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder is 5 μm.

[0217] [Comparative Example 3]

[0218] The preparation process of the lithium ion battery of Comparative Example 3 is substantially the same as that of Example 1, except that the second active material is natural graphite.

[0219] [Comparative Example 4]

[0220] The preparation process of the lithium-ion battery of Comparative Example 4 is basically the same as that of Example 1, except that there is no second active material, and the weight ratio of the first active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-walled CNT, the binder styrene acrylic emulsion (SAR), and the thickener CMC-Na is 94.9%:1%:0.1%:3%:1%.

[0221] 2). Performance characterization of negative electrode sheets of lithium-ion batteries

[0222] 2.1) Measurement of volume average particle size Dv50: It can be tested with a laser particle size analyzer (such as Master Size 3000) according to GB / T 19077-2016 particle size distribution laser diffraction method.

[0223] 2.2) Measurement of porosity: refer to GB / T 24586-2009;

[0224] Pretreatment: Use tweezers to select more than 20 original pieces with good appearance and no powder falling on the edges and put them into the sample cup, record the number of pieces, and calculate the apparent volume;

[0225] Measurement: Place the sample cup containing the sample in a true density tester in a closed test system, introduce helium according to the program, detect the pressure of the gas in the sample chamber and the expansion chamber, and then calculate the true volume according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested.

[0226] 2.3) Measurement of compaction density: For details, refer to GB / T 24533-2009. Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, weigh the weight of the powder m, and set the pressure to 400kN. The thickness (thickness after unloading) and volume v of the powder can be read on the equipment, and the compaction density can be calculated by ρ=m / v.

[0227] 2.4) Measurement of total pore volume: refer to GB / T 19587-2004 for details, adopt mesopore pore size distribution test BJH (Barret joyner Halenda), use gas adsorption and desorption method to test under micro-mesopore model and select adsorption branch data, respectively measure and count the total pore volume V1 of pores with pore diameter greater than 100nm and the total pore volume V2 of pores with pore diameter less than or equal to 100nm.

[0228] 2.5) Measurement of specific surface area SSA: It can be measured by referring to GB / T 19587-2017, using the inert gas (such as nitrogen) adsorption specific surface area analysis test method and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed using the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.

[0229] Table 1 Specific experimental parameters of Examples 1-20 and Comparative Examples 1-4

[0230]

[0231]

[0232] 3). Lithium-ion battery performance characterization

[0233] 3.1) Cycle performance test: At 45°C, keep the battery charge and discharge voltage range at 2.5-4.35V, cycle at 1C current density, and record the battery capacity retention rate after 500 cycles. The test results are shown in Table 2.

[0234] 3.2) Energy density test: At room temperature, charge to 4.35V at a current density of 0.5C, then discharge 5 to 2.5V, record the energy density during the discharge process; repeat three times and calculate the average discharge energy E. Weighing lithium ions

[0235] The mass of the battery is M, and the energy density of the lithium-ion battery is calculated as GED=E / M. The measurement results are shown in Table 2.

[0236] 3.3) Power performance test: Under normal temperature conditions, the battery is fully charged at a current density of 1C, and then discharged at a current density of 4C. The discharge time of the battery is recorded. The measurement results are shown in Table 2.

[0237] Table 2 Performance tests of Examples 1-20 and Comparative Examples 1-4

[0238]

[0239]

[0240] In the embodiment of the present application, the cycle performance of the battery can be characterized by the capacity retention rate after 500 cycles. The higher the capacity retention rate after 500 cycles, the better the cycle performance of the battery. The rate performance of the battery can be characterized by the discharge time under 4C. The longer the discharge time, the slower the battery decays and the better the rate performance of the battery.

[0241] It can be seen from Examples 1-16 and Comparative Examples 3 and 4 that adding silicon-based materials to the negative electrode film layer helps to improve the energy density and rate performance of the battery.

[0242] It can be seen from Examples 1-16 and Comparative Examples 1 and 2 that adding a binder with a particle size of 0.1-0.8 μm to the negative electrode film layer is beneficial to improving the cycle performance of the battery while maintaining a higher energy density and better rate performance.

[0243] According to Examples 1-5, adding 0.1-0.5 μm, especially 0.1-0.3 μm, of a binder to the negative electrode film layer is beneficial for further enabling the battery to have better cycle performance, higher energy density and better rate performance.

[0244] According to Examples 1 and 6-8, adding 1-5 parts by weight of a binder to the negative electrode film layer, that is, the mass proportion of the binder in the negative electrode film layer is 1%-5%, is beneficial to further enable the battery to have better cycle performance, higher energy density and better rate performance.

[0245] According to Examples 1, 9-10, various binders can improve the cycle performance of the battery, so that the battery has good cycle performance, high energy density and good rate performance.

[0246] According to Examples 1, 11 and 12, adding 25-50 parts by weight of silicon-based material to the negative electrode film layer, that is, the mass proportion of silicon-based material in the negative electrode film layer is 25%-50%, is beneficial to further improve the energy density and rate performance of the battery.

[0247] It can be seen from Examples 1, 14, 15 and Comparative Examples 3-4 that a variety of silicon-based materials can play a role in improving the energy density and rate performance of batteries.

[0248] According to Examples 1 and 16, adding graphite to the negative electrode film layer is beneficial to improving the cycle performance of the battery.

[0249] According to Examples 1 and 17, it can be seen that introducing hydrophilic groups into the binder is beneficial to further improve the cycle performance and rate performance of the battery.

[0250] According to Examples 1, 18-19, a variety of hydrophilic groups are applicable to the technical solution of the present application.

[0251] According to Examples 1 and 20, the specific surface area of ​​the second active material is 2-10 m 2 / g, especially 2-4m 2 / g, can improve battery performance.

[0252] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A negative electrode plate, characterized in that: include: A negative electrode current collector and a negative electrode film layer provided on at least one side of the negative electrode current collector; The negative electrode film layer comprises a negative electrode active material and a binder, wherein the negative electrode active material comprises a silicon-based material; Wherein, the volume average particle size Dv50 of the binder is 0.1-0.8 μm.

2. The negative electrode sheet according to claim 1, characterized in that: The volume average particle size Dv50 of the binder is 0.1-0.5 μm. Optionally, the volume average particle size Dv50 of the binder is 0.1-0.3 μm.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: Based on 100 parts by weight of the negative electrode film layer, the weight of the binder is 1-5 parts by weight. Optionally, the weight of the binder is 2-4 parts by weight.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The porosity of the negative electrode plate is 15%-60%. Optionally, the porosity of the negative electrode plate is 20%-45%.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The binder contains a hydrophilic group; Optionally, the hydrophilic group includes at least one of a sulfonic acid group, a phosphoric acid group, a hydroxyl group, a carboxyl group, an amide group, an amino group, an aldehyde group, a carbonyl group, a cyano group, and an acid anhydride.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The silicon-based material includes at least one of the following functional groups: carboxyl, hydroxyl, aldehyde, and carbonyl.

7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The specific surface area SSA of the silicon-based material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 2m 2 / g≤SSA≤4m 2 / g.

8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The volume average particle size Dv50 of the silicon-based material is 5-20 μm. Optionally, the volume average particle size Dv50 of the silicon-based material is 8-15 μm.

9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The silicon-based material comprises: Carbon matrix particles, the carbon matrix particles comprising a three-dimensional network cross-linked pore structure; and At least a portion of the silicon-based nanoparticles is disposed in the three-dimensional network cross-linked pore structure.

10. The negative electrode sheet according to claim 9, characterized in that: When the gas adsorption and desorption method is used for testing, the total pore volume of the pores with a pore size greater than 100 nm in the carbon matrix particles is recorded as V1 cm 3 / g, then V1≥0.01, optionally, 0.01≤V1≤0.5; and / or, When the gas adsorption and desorption method is used for testing, the total pore volume of the pores with a pore diameter of less than or equal to 100 nm in the carbon matrix particles is recorded as V2 cm 3 / g, then V2≥0.05, optionally, 0.05≤V2≤1.

1.

11. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The silicon-based material includes at least one of a silicon-carbon material and a composite of a silicon-carbon material and a silicon-oxygen material.

12. The negative electrode sheet according to claim 11, characterized in that: The silicon-oxygen material includes SiOx, wherein 0.4≤x≤1.

6.

13. The negative electrode sheet according to claim 11 or 12, characterized in that: The silicon-carbon material comprises a silicon-carbon composite; Based on the total mass of the silicon-carbon composite, a ratio of a mass content B of carbon element to a mass content A of silicon element in the silicon-carbon composite is 1.3≤B / A≤2.

14. The negative electrode sheet according to any one of claims 1 to 13, characterized in that: The binder includes at least one of polystyrene butadiene copolymer and its modified products, polystyrene-acrylate and its modified products, polyacrylate copolymer and its modified products, polyurethane copolymer and its modified products, butadiene and acrylonitrile copolymer and its modified products, polytetrafluoroethylene and its modified products, polyvinylidene fluoride and its modified products.

15. The negative electrode sheet according to any one of claims 1 to 14, characterized in that: Based on 100 parts by weight of the negative electrode film layer, the weight of the silicon-based material is 25-50 parts by weight. Optionally, the weight of the silicon-based material is 30-40 parts by weight.

16. The negative electrode sheet according to any one of claims 1 to 15, characterized in that: The negative electrode active material also includes graphite; Wherein, based on 100 parts by weight of the negative electrode film layer, the weight of the graphite is 45-70 parts by weight, and optionally, the weight of the graphite is 55-65 parts by weight.

17. The negative electrode sheet according to any one of claims 1 to 16, characterized in that: The compaction density of the negative electrode plate is 1.0-2.2 g / cm 3 Optionally, the compaction density of the negative electrode plate is 1.2-1.8 g / cm 3 .

18. The negative electrode sheet according to any one of claims 1 to 17, characterized in that: The thickness of the negative electrode plate is 60-150 μm. Optionally, the thickness of the negative electrode plate is 90-130 μm.

19. A battery cell, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 1 to 18.

20. The battery cell according to claim 19, characterized in that: The battery cell further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material.

21. The battery cell according to claim 20, characterized in that: The positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.

02.

22. A battery, characterized in that: The invention comprises the battery cell according to any one of claims 19 to 21.

23. An electrical device, characterized in that: Comprising a battery as claimed in claim 22.

Citation Information

Patent Citations

  • Pole piece, electrochemical device and electronic device

    CN113692654A

  • Negative electrode slurry composition and application

    CN114583173A

  • Negative electrode material as well as negative electrode plate and battery comprising negative electrode material

    CN114864909A

  • Electrochemical device and electronic device

    CN115516682A

  • Binder, negative pole piece, electrochemical device and electronic device

    CN116195084A

Cited By

  • Negative pole piece, battery, energy storage device and electric equipment

    CN120072947A

  • Negative electrode sheet, battery cell, battery, and electrical device

    EP4651237A1

  • Battery and electric apparatus

    WO2026016560A1

  • Secondary battery cell, secondary battery, and electric device

    WO2026144382A1